2014
DOI: 10.1186/1478-4491-12-72
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of training and deployment policies for human resources for health for maternal, newborn, and child health in rural Africa

Abstract: BackgroundMost African countries are facing a human resources for health (HRH) crisis, lacking the required workforce to deliver basic health care, including care for mothers and children. This is especially acute in rural areas and has limited countries’ abilities to meet maternal, newborn, and child health (MNCH) targets outlined by Millennium Development Goals 4 and 5. To address the HRH challenges, evidence-based deployment and training policies are required. However, the resources available to country-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 67 publications
(81 reference statements)
1
14
0
1
Order By: Relevance
“…Our findings especially, on the availability of the policy and system-relevant documents are supported by literature from previous studies in low- and middle-income countries [ 26 , 27 ]. We found out that apart from “other reports”, rapid response summaries were by far the most dominant type of documents produced, although most of them were produced in a particular period, from 2008 to 2013.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings especially, on the availability of the policy and system-relevant documents are supported by literature from previous studies in low- and middle-income countries [ 26 , 27 ]. We found out that apart from “other reports”, rapid response summaries were by far the most dominant type of documents produced, although most of them were produced in a particular period, from 2008 to 2013.…”
Section: Discussionsupporting
confidence: 87%
“…This may instead point to the fact that these documents were not readily on governmental and NGOs’ websites: an indication for lack of one-stop shops for knowledge sharing in the country. This is supported by findings from a study by Murphy [ 27 ], which demonstrated that information on training and deployment policies for health workers for maternal, newborn and child health in rural Africa was not available on governmental websites; it was instead readily located on the sites of institutions with a greater capacity for knowledge sharing. Generally, there was a noted increase in the number of documents from 6 documents per year in 2000 to 49 per year in 2011, dropping in the following years.…”
Section: Discussionmentioning
confidence: 52%
“…To the best of our knowledge, this study is one of the first to quantitatively investigate this relationship, especially in regions with high rates of maternal death. Although there is evidence in the global literature that the increased density of human resources (especially nurses, specialists and non-specialist doctors) reduces maternal, infant and child mortality [ 19 , 20 ], there has been limited specific investigation in many African countries aimed at testing this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Face à la pénurie inquiétantederessources humaines en Afrique, les recherchessur lesfacteursinfluençant la rétention desprofessionnelsdelasanté en milieu rural se sont multipliées. Elles ont toutes en grande partie tenté d'éclairer lesp rises de décisions politiques pour renforcer la place des ressources humaines au sein du système de santé [22][23][24]. Ces recherches s'accordentsur le fait que la motivation dans le cadrep rofessionnel est un phénomène complexe et dynamique car elle évolue dans le temps, change en fonction du contexte et est influencée par une multitude de facteurs situés à différents niveaux (macro : politiques,contexte institutionnel, conditions de vie), individuel (satisfactionp rofessionnelle, situation familiale, genre), organisationnel( conditions de travail) [12] mais essentiel à comprendrepour mettreenbranle lesréformes nécessairesenAfrique subsaharienne [13][14][15].…”
Section: Discussionunclassified